Quality nursing care in Australian paediatric hospitals: A Delphi approach to identifying indicators - Wilson, Sally; Hauck, Yvonne; Bremner, A.; Finn, J. (Wiley-Blackwell Publishing Ltd., 2012)
Aim: To identify indicators of quality nursing care by identifying structures, processes and outcomes perceived as valid, feasible, reliable and suitable for Australian paediatric hospitals by nursing experts. Background: Although measuring the quality of nursing care in acute care settings is being practised, there are few indicators validated for use in paediatric nursing. Using adult indicators for quality care measures in children’s nursing has inherent problems. To contribute to quality improvement and safety in the paediatric population, it is essential to identify and validate indicators that will be useful in this context. Design: A modified Delphi technique. Method: Fifty-seven indicators that potentially measure the quality of nursing care in paediatrics were identified following a review of the literature. Three online surveys where panellists rated these indicators for perceived validity in paediatric nursing, feasibility of data collection, reliability based on existing documentation and suitability in the paediatric context were completed between March–May 2010. Results: Fifty-two nurses contributed to the expert panel. Consensus of 75% for validity in paediatric nursing was reached on 42 indicators, which were then ranked for suitability of use. Nineteen indicators were deemed inappropriate, which included indicators commonly used in adult settings.Conclusion: Face and content validity were reached for 42 indicators identified as potential valid measures of quality care in paediatric nursing. Further work is required to solve issues of reliability and feasibility of data collection and to ascertain whether the indicators occur frequently enough within Australian hospitals to be clinically useful. Relevance to clinical practice: Identification of nursing-sensitive indicators that are valid in the paediatric setting is the first step in measuring the quality of care provided to children. Once established, measurement of the indicators may lead to improved patient safety and care in hospitals.